Pengaruh Penerapan Sistem Pemerintahan Berbasis Elektronik Terhadap Peningkatan Kinerja Pegawai pada Dinas Perindustrian dan Perdagangan, Provinsi Sumatera Utara - Dian Jatikusuma; Isnaini Isnaini; Budi Hartono (Mahesa Research Center, 2023)
The purpose of this study was to determine the effect of differences between the quantity, quality of work, timeliness and employee performance before the implementation of the Electronic Based Government System and the quantity, quality of work, timeliness and employee performance after e-government based at the Department of Industry and Trade North Sumatra Province. To analyze the research objectives, the 3 dimensions of performance contained in Dharma theory are used: namely, quantity of work, quality of work and timeliness. This study uses a quantitative approach, because in this study the relationship between variables is causal and in addition to testing the hypothesis between competency variables on performance. While the type of research used is included in the explanatory research type. namely research that is used to obtain data from certain places, using questionnaires as primary data. The results of the study found that the Implementation of Electronic-Based Government Systems gave increased performance based on the aspect of work quantity; provide performance improvement based on work quality aspects; provide performance improvement based on timeliness aspect; and provide performance improvement based on employee performance aspects.